Optimal Team Size and Monitoring in Organizations - Liang, Pierre Jinghong; Rajan, Madhav V.; Ray, Korok (The Accounting Review, 2008)
We formulate and analyze a model of team structure and monitoring within a Linear-Exponential-Normal (LEN) agency framework. We incorporate three key instruments in the internal design of an organization involving team production: team size, monitoring activities, and incentive contracts. We show that the complex tradeoffs among these instruments lead to surprisingly simple implications. One such result is that the equilibrium level of pay-for-performance for workers is attenuated and is, at times, invariant to most environmental variables of interest. As such, our model helps explain the empirical puzzle of the lack of a trade-off for risk/incentives shown in standard agency models. Our work also demonstrates the presence of complementarities between team size and monitoring, and between worker talent and managerial monitoring ability. Finally, we derive predictions about the impact of environmental variables on the choice of optimal team size, incentives, and employee quality, even in the presence of an external marketplace for talent.